Performance enhancement of heat recovery from engine exhaust gas using corona wind - Shin, Dong Ho; Kim, Sunuk; Ko, Han Seo; Shin, Youhwan (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
This study develops a new type of heat exchanger with tungsten wires to produce a corona wind. Experimental data are presented for the velocity and temperature of the corona flow from wires to parallel electrodes with respect to the applied voltage and power. Additionally, a gas engine power generation system is manufactured, and its power generation efficiency is tested according to the fuel gas volume fraction between methane and carbon dioxide. Furthermore, an exhaust gas heat recovery system is fabricated using the proposed heat exchanger. A prototype of the corona wind heat exchanger is manufactured, and its enhanced heat recovery efficiency is tested with the gas engine. The corona wind heat exchanger operates well under the available exhaust gas conditions; it increases the temperature of 1 L/min water flow by 45 degrees C by recovering 2 kW of heat energy from the exhaust gas. The total power production efficiency was increased from 29% to 47%. The results confirm that the proposed corona wind heat exchanger can be applied to the gas engines to greatly enhance their heat recovery efficiency.
Keywords: EXPERIMENTAL OPTIMIZATION; RANKINE-CYCLE; IONIC WIND; EXCHANGER; SYSTEM; SHELL; GENERATOR